2004
DOI: 10.4049/jimmunol.172.1.292
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell Maturation Controls Adhesion, Synapse Formation, and the Duration of the Interactions with Naive T Lymphocytes

Abstract: The initiation of adaptive immune responses requires the direct interaction of dendritic cells (DCs) with naive T lymphocytes. It is well established that the maturation state of DCs has a critical impact on the outcome of the response. We show here that mature DCs form stable conjugates with naive T cells and induce the formation of organized immune synapses. Immature DCs, in contrast, form few stable conjugates with no organized immune synapses. A dynamic analysis revealed that mature DCs can form long-lasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(128 citation statements)
references
References 44 publications
4
122
0
2
Order By: Relevance
“…As maturation, DCs lose their endocytic ability, up-regulate MHC class II and costimulatory molecules, and present antigen to T cells for the initiation of immune responses [11]. DCs influence T cell proliferation and effector function by providing costimulation and establishing the cytokine environment at the time of T cell priming [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As maturation, DCs lose their endocytic ability, up-regulate MHC class II and costimulatory molecules, and present antigen to T cells for the initiation of immune responses [11]. DCs influence T cell proliferation and effector function by providing costimulation and establishing the cytokine environment at the time of T cell priming [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the direction of T cells polarization determined the prognosis of many infectious diseases and cancers. In cancer patients with high expression of the Th1 cells had a prolonged disease-free survival [10], while with high expression of the Th2 cells, the patients had a poor progressive [11]. It was reported that Th1 immunity was compromised in infections, while enhancing Th1 responses improved the anti-inflammatory effect [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The activation status of dendritic cells (DCs) is a critical determinant of the outcome of Ag recognition by T cells (11,12). Ag presentation by immature DCs often results in tolerance, whereas mature DCs are associated with the priming of T cell populations (11,13,14).…”
Section: Ifferent Subsets Of Effector Cd4mentioning
confidence: 99%
“…It was not surprising to find that tumor-treated DCs could achieve less DCs-dependent T cell proliferation and antigen-specific CTL priming. As IL-12 is one of the key mediators of signal 3 to promote Th1-cell or CTL development (33), the decrements of IL-12 secretion and effectors CTL priming in our data might indicate that tumor cells-incubated DCs failed to induce the differentiation of T cells with full function (34).…”
Section: Discussionmentioning
confidence: 68%